A Sulfite Respiration Pathway from Thermus thermophilus and the Key Role of Newly Identified Cytochrome c(550) - Robin, Sylvain (American Society for Microbiology, 2011)

(untitled)
Sulfite, produced for instance during amino acid metabolism, is a very reactive and toxic compound. Various detoxification mechanisms exist, but sulfite oxidoreductases (SORs) are one of the major actors in sulfite remediation in bacteria and animals. Here we describe the existence of an operon in the extreme thermophilic bacterium Thermus thermophilus HB8 encoding both a SOR and a diheme c-type cytochrome. The in vitro analysis clearly showed that the newly identified cytochrome c(550) acts as an acceptor of the electrons generated by the SOR enzyme during the oxidation of sulfite. The electrons are then rapidly shuttled via cytochrome c(552) to the terminal ba(3)- and caa(3)-type oxidases, thereby unveiling a novel electron transfer pathway, linking sulfite oxidation to oxygen reduction in T. thermophilus: sulfite → SOR(HB8) → cytochrome c(550) → cytochrome c(552) → ba(3) oxidase/caa(3) oxidase → O(2). The description of the complete pathway reveals that electrons generated during sulfite oxidation by the SOR are funneled into the respiratory chain, participating in the energy production of T. thermophilus.